O imaginário do aluno sobre a língua inglesa na constituição de sua subjetividade - Oliveira, Pauliana Duarte (2006)
The contact with students of basic education in public schools led us to notice that these students, generally, enunciate the English language in a contradictory way. At the same time that they don t feel motivated with the lessons of English language at the school where they study, the same students circumscribe their saying in discourses of exaltation to the English language. The way as the contact with the English language in the context of public school happens is not enough a capable condition to promote a learning considered satisfactory. However, from this contact senses and representations are produced about the English language. Such representations are raised by the discourses that circulate in the historical and social space and they are present in the imaginary of these students, producing in some way, effects in their subjectivities and leading them to circumscribe their saying in a discoursive way in these discourses. The focus of our work is to try to understand this contradiction in student s saying: how does the student exalt a language which he or she practically does not have contact? We carried out interpretative and descriptive analysis of the corpus, made up of interviews half-structuralized with students and teachers of English language of the public school objectifying to investigate the role of the student s imaginary on the English language in the constitution of the subjectivity. The interdiscourse related to the status of the English language in the world and to the politics of education of foreign language contributes to explain the contradiction of the students saying, therefore if interdiscourse shows respect to the deriving discourses of different places and different ages, it is inferred from there that the student s discoursive production contains contraditions.